Parastrophic quasigroup string processing - Popovska-Mitrovikj, Aleksandra; Bakeva, Verica; Dimitrova, Vesna (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University in Skopje, Macedonia, 2011)
In this paper, we propose a new quasigroup string transformation based on quasigroup parastrophes. Using the proposed quasigroup string transformation, a new classification of quasigroups of order 4 is given.
Keywords: quasigroup, string transformation, parastrophe, parastrophic fractal and parastrophic non-fractal quasigroup